Substrate-Assisted Formation of ZIF-8 Crystals for Tunable Size and Morphological Characteristics: Investigating the Role of Temperature, Method, and Solvent on the Size of ZIF-8 Crystals - Shubhangi; Dhayal M. (My University, 2025)
Metal–Organic Frameworks (MOFs) are an eminent class of 3D porous structures such as Zeolitic imidazolate frameworks (ZIFs), which have been into the research limelight lately due to their diverse functionalities and surface properties. This report discusses a new method for substrate-assisted synthesis of ZIF-8 with control over its crystallite structure, size and uniformity on different substrates. The study elaborately focuses on morphology depiction through scanning electron microscopy (SEM) analyses, which confirmed the initiation of crystal synthesis on substrate like Indium Tin oxide (ITO) at as less as 1.5 h. This is the first report that uses such minimal time for ZIF-8 MOF to attain complete hexagonal morphology at the earliest 3 h at high temperature. The study also compares the results for ZIF-8 synthesis, which required double the time when done in solution phase in the absence of substrate. The findings also confirm a relatively high proportion of distorted ZIF-8 particles in solution than those synthesized in the presence of substrates, like glass and ITO, possessing relatively high yield with better arrangement of crystals. This study can pave the path for future application of ZIF-8 as a substrate for dye sorption and contaminant elimination from wastewater. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2025.